1995
DOI: 10.1007/bf00635871
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Na+, K+-adenosinetriphosphatase, citrate synthase and K+ in sheep skeletal muscle during immobilization and remobilization

Abstract: The K+ balance and muscle activity seem to interact in a complex way with regard to regulating the muscle density of Na(+)-K+ pumps. The effect of immobilization was examined in ten sheep that had low muscle K+ content. Three additional sheep served as untreated controls. After being brought from pasture to sheep stalls one hindlimb was immobilized in a plaster splint for 9 weeks, and in five of the animals remobilization was carried out for a further 9 weeks. The weight bearing of the leg in plaster was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Unfortunately, it is unclear whether participants in that study also suffered significant deficiencies to their skeletal muscle (such as reductions in fiber area), although further work by that group has shown that chronic heart failure induces reductions in capillary density and a higher predominance of type IIx fibers. 11 In other studies, 23,24 and the present study, the skeletal muscles of the participants were certainly affected as evidenced by accompanying muscle atrophy. The fact that skeletal muscle Na ϩ ,K ϩ -ATPase reductions were greater in the present study than in the two aforementioned studies 23,24 suggests that functional denervation, per se, has a specifically devastating effect on Na ϩ ,K ϩ -ATPase expression in addition to the effects of disuse alone.…”
Section: Skeletal Muscle Namentioning
confidence: 73%
See 3 more Smart Citations
“…Unfortunately, it is unclear whether participants in that study also suffered significant deficiencies to their skeletal muscle (such as reductions in fiber area), although further work by that group has shown that chronic heart failure induces reductions in capillary density and a higher predominance of type IIx fibers. 11 In other studies, 23,24 and the present study, the skeletal muscles of the participants were certainly affected as evidenced by accompanying muscle atrophy. The fact that skeletal muscle Na ϩ ,K ϩ -ATPase reductions were greater in the present study than in the two aforementioned studies 23,24 suggests that functional denervation, per se, has a specifically devastating effect on Na ϩ ,K ϩ -ATPase expression in addition to the effects of disuse alone.…”
Section: Skeletal Muscle Namentioning
confidence: 73%
“…11 In other studies, 23,24 and the present study, the skeletal muscles of the participants were certainly affected as evidenced by accompanying muscle atrophy. The fact that skeletal muscle Na ϩ ,K ϩ -ATPase reductions were greater in the present study than in the two aforementioned studies 23,24 suggests that functional denervation, per se, has a specifically devastating effect on Na ϩ ,K ϩ -ATPase expression in addition to the effects of disuse alone.…”
Section: Skeletal Muscle Namentioning
confidence: 73%
See 2 more Smart Citations
“…Leg immobilization in sheep for 9 wk is associated with a 39% reduction in Na ϩ -K ϩ -ATPase abundance in the vastus lateralis muscle (28). In rats, [ 3 H]ouabain binding capacity in soleus muscle is decreased 22% after 7 days of denervation (11).…”
Section: E867mentioning
confidence: 99%